Peningkatan Pemahaman Santri Kelas Shifir Tsani Terhadap Materi I'lal Melalui Metode Pembelajaran Kooperatif Di Madrasah Diniyah RoudlotuThalibin - Robbiah Ratna Swari Hibbatullah; Choirun Nisa’; Devi Habibi Muhammad; Wardhatus Sa’adah (Education Reserach Center, 2025)
This study aims to improve the comprehension of Shifir Tsani class students at Madrasah Diniyah Roudlotut Thalibin on the Arabic linguistic concept of I’lal through the application of a cooperative learning model integrating discussion methods. Using the Classroom Action Research (CAR) model by Kemmis and McTaggart, the study involved sixteen students divided into four groups across two learning cycles. The first cycle employed discussion based learning, yielding 25% of students in the “excellent” category, 62.5% “good,” and 12.5% “fair.” After refining the instructional design with inquiry-based strategies and interactive media in the second cycle, results improved significantly, with 93.75% achieving “excellent” and all meeting the Minimum Mastery Criteria. The findings confirm that cooperative inquiry learning effectively enhances conceptual understanding, motivation, and engagement. Theoretically, the results reinforce Social Constructivism (Vygotsky), Cooperative Learning (Johnson & Johnson), and Inquiry Learning (Bruner) as frameworks for meaningful and collaborative learning in Islamic education